Genome-Wide Identification and Characterization of the SHI-Related Sequence Gene Family in Rice. (September 2020) - Yang, Jun; Xu, Peng; Yu, Diqiu
Rice ( Oryza sativa ) yield is correlated to various factors. Transcription regulators are important factors, such as the typical SHORT INTERNODES-related sequences (SRSs), which encode proteins with single zinc finger motifs. Nevertheless, knowledge regarding the evolutionary and functional characteristics of the SRS gene family members in rice is insufficient. Therefore, we performed a genome-wide screening and characterization of the OsSRS gene family in Oryza sativa japonica rice. We also examined the SRS proteins from 11 rice sub-species, consisting of 3 cultivars, 6 wild varieties, and 2 other genome types. SRS members from maize, sorghum, Brachypodium distachyon, and Arabidopsis were also investigated. All these SRS proteins exhibited species-specific characteristics, as well as monocot- and dicot-specific characteristics, as assessed by phylogenetic analysis, which was further validated by gene structure and motif analyses. Genome comparisons revealed that segmental duplications may have played significant roles in the recombination of the OsSRS gene family and their expression levels. The family was mainly subjected to purifying selective pressure. In addition, the expression data demonstrated the distinct responses of OsSRS genes to various abiotic stresses and hormonal treatments, indicating their functional divergence. Our study provides a good reference for elucidating the functions of SRS genes in rice.